2021
DOI: 10.3390/coatings11060728
|View full text |Cite
|
Sign up to set email alerts
|

Impact Evaluation of High Energy Ball Milling Homogenization Process in the Phase Distribution of Hydroxyapatite-Barium Titanate Plasma Spray Biocoating

Abstract: Air plasma spray technique (APS) is widely used in the biomedical industry for the development of HA-based biocoatings. The present study focuses on the influence of powder homogenization treatment by high-energy ball milling (HEBM) in developing a novel hydroxyapatite-barium titanate (HA/BT) composite coating deposited by APS; in order to compare the impact of the milling process, powders were homogenized by mechanical stirring homogenization (MSH) too. For the two-homogenization process, three weight percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Only recently was plasma spray deposition successfully used for coatings of HAp and barium titanate. The results showed that none of the materials were modified by the coating process [31,32] In this work, a comparative study was conducted using samples of uncoated Ti-6Al-4V plates, samples coated with HAp by CoBlast TM (CB HAp), Plasma Spray (PS HAp), 80%/20% (m/m) HAp/BaTiO 3 using non-piezoelectric cubic nanopowders (HAp/cBT) and piezoelectric tetragonal micropowders (HAp/tBT) by CoBlast TM . Materials were characterised to find if any phase changes occurred and if by-products of the deposition appeared.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently was plasma spray deposition successfully used for coatings of HAp and barium titanate. The results showed that none of the materials were modified by the coating process [31,32] In this work, a comparative study was conducted using samples of uncoated Ti-6Al-4V plates, samples coated with HAp by CoBlast TM (CB HAp), Plasma Spray (PS HAp), 80%/20% (m/m) HAp/BaTiO 3 using non-piezoelectric cubic nanopowders (HAp/cBT) and piezoelectric tetragonal micropowders (HAp/tBT) by CoBlast TM . Materials were characterised to find if any phase changes occurred and if by-products of the deposition appeared.…”
Section: Introductionmentioning
confidence: 99%